Study on Friction and Wear Behavior of Inconel 625 Superalloy during Hot Extrusion - Yanjiang Wang; Sixiang Zhao; Zhi Jia; Jinjin Ji; Dexue Liu; Tingbiao Guo; Yutian Ding (Advances in Materials Science and Engineering, 2020)
Friction during the hot extrusion of Inconel 625 superalloy tubes causes severe wear of the mold and plays a decisive role in the quality of the workpieces. In this paper, a ball-to-disk method was utilized to investigate the tribological behavior of Inconel 625 using two different tribological pairs, i.e., GCr15 and Si3N4, at room and elevated temperatures. Friction coefficient, specific wear rate, and morphology of worn surfaces were systematically characterized. It was found that the friction coefficients for both tribological pairs generally increased as the testing temperature increased, while the specific wear rate increased firstly and then decreased with the rise of temperature. Along with the increasing sliding speed, the friction coefficient between Inconel 625 and Si3N4 decreased monotonically, while the specific wear rate increased firstly and then decreased. Under any given testing condition, the friction coefficient and specific wear rate of the Inconel 625 for Inconel/Si3N4 pair are less than those of the Inconel/GCr15 pair. The main wear mechanisms between GCr15 and Inconel 625 are adhesive and fatigue wear at all testing temperatures. The wear mechanisms between Si3N4 and Inconel 625 are adhesive and abrasive wear at room temperature but fatigue wear at 500°C. Our findings indicate that the use of ceramic molds in the hot extrusion of Inconel 625 may significantly improve the surface qualities of the product and reduce the wear of the mold.